Mucocele of the appendix and laparoscopic treatment [Appendiks mukoseli ve laparoskopik tedavisi] - (:unkn) unknown (AVES, 2010)
Purpose: To diagnose and describe the appendicular mucocele and its importance and possible complications, and also to show the laparoscopic approach in this disease, against the known, open surgical procedure. Methods: The appendicular mucocele was diagnosed in a patient by abdominal ultrasonography and abdominal MR imaging techniques in our clinic. Afterwards it was decided to perform a surgical operation and laparoscopic approach was planned. With the use of laparoscopic endobag and sufficient surgical technique, mucocele of the appendix was taken out of the abdomen without causing any perforation. Results: By the laparoscopic approach in this patient, using a laparoscopic endobag, the appendicular mucocele was not ruptured. And the mucous material inside the appendicular mucocele did not contaminate the abdominal cavity, which would have caused pseudomyxoma peritonei. Conclusion: Altough there is a risk of pseudomyxoma peritonei in appendicular mucocele, the surgical procedure may be achieved by laparoscopic approach with the use of appropriate devices and sufficient surgical experience.
Keywords: Appendectomy; Appendix; Laparoscopic surgery; Mucocele; Pseudomyxoma peritonei